Future of Decellularized Dental Pulp Matrix in Regenerative Endodontics - Khurshid, Zohaib; Alnaim, Ahmed Jamil Ahmed; Alhashim, Ahmed Abdulhakim Ahmed; Imran, Eisha; Adanir, Necdet (European Journal of Dentistry, 2022)
With the advancements in tissue engineering, the repair and regeneration of oral/dental tissue are becoming possible and productive. Due to periodontal diseases, the tooth loses bone support resulting in tooth loss, but bone grafting stabilizes with new bone. It is seen that due to the progression of dental caries, pulp damage happens, and the vitality of the tooth is compromised. The current theme of dental pulp regeneration through biological and synthetic scaffolds, is becoming a potential therapy for pulp revitalization.
Keywords: tooth; dental pulp tissue; root canal treatment; decellularization; regenerative endodontics